Pronounced Enhancement in Radiosensitization of Esophagus Cancer Cultivated in Docosahexaenoic Acid via the PPAR -γ Activation - Yang, Ying; Xu, Ying; Zhao, Congzhao; Zhang, Lirong; Nuerbol, Aslibek; Wang, Lili; Jiao, Yang (Frontiers in Medicine, 2022)
Docosahexaenoic acid (DHA) has been reported to slow the tumor growth and improve prognosis, and been used to co-operate with many other chemotherapy medicines. Up to now, surveys focused on the interaction between DHA and radiation is relatively modest. Our study sought to evaluate the radiosensitivity changes caused by DHA on esophageal cancer cells. We selected TE-1 and TE-10 esophagus cancer cell as models, and performed routine cell proliferation assay and cloning assay to detect the impact of DHA combined with X-ray. Cell cycle assay, lipid peroxidation assay, comet assay and apoptosis assay were carried out to unearth the potential causes, mouse transplanted tumor experiment was also launched to verify the synergetic effect of DHA and irradiation. At last, western blot assay was used to find novel mechanism. As a result, DHA improved TE-1 and TE-10 radiosensitivity both in vivo and in vitro. What’s more, PPAR -γ expression increased due to the DHA supplement, inhibit PPAR -γ could attenuate benefits brought out by DHA somehow. Due to its explicitly usage and convenient, DHA and other PPAR -γ agonists would serve as an adjuvant therapy before radiotherapy if the clinical trials indicated positive from now on.